The Effect of Physical Exercise On Changes The Blood Pressure of The Elderly in The Village of Narmada West Lombok - Purqoti, Dewi Nur Sukma (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Physical exercise is one of the most effective efforts in controlling blood pressure. High blood pressure is a problem that is still widely found in developing countries. The purpose of this study was to see the effect of physical exercise on changes the blood pressure of the elderly in the village of narmada west Lombok. The design of this study uses pre-experimental with crossectional approaches. The samples in this study were 16 people. Analyze the data using the paired t test. The results of this study showed a p-value=0.00 (p<0.05). There was a difference between blood pressure in the elderly before and after physical exercise.